2009
DOI: 10.1007/s00122-009-1028-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of highly variable chloroplast sequences and development of cpDNA-based molecular markers that distinguish four cytoplasm types in radish (Raphanus sativus L.)

Abstract: Four types of cytoplasms (Ogura, DCGMS, DBRMF1, and DBRMF2) were identified in the previous studies using molecular markers based on mitochondrial genome variations in radish (Raphanus sativus L.). However, mtDNA markers have limitations in obtaining clear results due to complexity of radish mitochondrial genomes. To improve fidelity, molecular markers based on variation of chloroplast genome sequences were developed in this study. We searched for the sequence variations of chloroplast genome among the four cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…However, the gene responsible for CMS in DCGMS may differ from the orf138 gene, since orf138 was detected as a sublimon in the DCGMS cytotype (Lee et al 2008). Furthermore, the phylogenetic relationship based on chloroplast sequence polymorphisms among the four cytotypes revealed that the DCGMS cytotype was very close to the male-fertile DBRMF2 cytotypes rather than the Ogura cytotype (Kim et al 2009a). In addition, the two CMS lines had different male-sterility phenotypes and pollen development patterns, and many restorer lines for Ogura CMS failed to restore fertility to DCGMS male-sterility (Lee et al 2008).…”
Section: Inheritance Pattern Of Fertility Restoration Of Cms Induced mentioning
confidence: 92%
See 2 more Smart Citations
“…However, the gene responsible for CMS in DCGMS may differ from the orf138 gene, since orf138 was detected as a sublimon in the DCGMS cytotype (Lee et al 2008). Furthermore, the phylogenetic relationship based on chloroplast sequence polymorphisms among the four cytotypes revealed that the DCGMS cytotype was very close to the male-fertile DBRMF2 cytotypes rather than the Ogura cytotype (Kim et al 2009a). In addition, the two CMS lines had different male-sterility phenotypes and pollen development patterns, and many restorer lines for Ogura CMS failed to restore fertility to DCGMS male-sterility (Lee et al 2008).…”
Section: Inheritance Pattern Of Fertility Restoration Of Cms Induced mentioning
confidence: 92%
“…One interesting feature of the male-fertile parental line (R171) is that this accession was introduced from Russia and contains DCGMS cytoplasm. The earliest identified male-sterile accession containing DCGMS cytoplasm was introduced from Uzbekistan ( Lee et al 2008), and a previous survey of four radish cytotype distribution showed that DCGMS cytotypes were predominantly identified from germplasm introduced from East European countries (Kim et al 2009a). Therefore, we assume that multiple restorer-of-fertility genes might exist in radish germplasm from European countries.…”
Section: Inheritance Pattern Of Fertility Restoration Of Cms Induced mentioning
confidence: 98%
See 1 more Smart Citation
“…The Brassicaceae family is estimated to consist of 338 genera and 3,700 species (Bailey et al 2006). Previous phylogenetic studies of the Brassicaceae family showed that radish was a relative of both Arabidopsis and Brassica species (Yang et al 1999;Kim et al 2009). In particular, radish was reported to be more closely related to Brassica rapa than other Brassica species when variations within the chloroplast genomes were used to construct phylogenetic trees (Warwick and Black 1997;Yang et al 2002;Kim et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous phylogenetic studies of the Brassicaceae family showed that radish was a relative of both Arabidopsis and Brassica species (Yang et al 1999;Kim et al 2009). In particular, radish was reported to be more closely related to Brassica rapa than other Brassica species when variations within the chloroplast genomes were used to construct phylogenetic trees (Warwick and Black 1997;Yang et al 2002;Kim et al 2009). However, when the phylogeny were analyzed using RFLP and random amplified polymorphic DNA (RAPD) techniques (Thormann et al 1994) or nuclear internal transcribed spacer (ITS) sequences (Yang et al 1999), radish was shown to be more closely related to B. nigra than B. rapa.…”
Section: Discussionmentioning
confidence: 99%